FEATURES OF MARKETING POLICY OF THE COMPANIES IN THE MARKET OF CONSULTING SERVICES - Timur A. Tultaev (Статистика и экономика)
Dynamic development of the market of consulting services against progressing competitive fight promoted strengthening of a role of marketing in the activity of the consultant companies. The given article is devoted to the analysis of marketing policy and features of its application in consulting business.